Airborne Aerosolized Mouse Cytomegalovirus From Common Otolaryngology Procedures: Implications for COVID‐19 Infection. (15th September 2020) - Sayahi, Tofigh; Nielson, Christopher; Yu, Yuan; Neuberger, Kaden; Seipp, Michael; Firpo, Matthew A.; Kelly, Kerry; Park, Albert H.
Abstract : Objectives: To determine whether common otolaryngology procedures generate viable aerosolized virus through a murine cytomegalovirus (mCMV) model for infection. Study Design: mCMV model of infection. Setting: University of Utah laboratory. Methods: Three‐day‐old BALB/c mice were inoculated with mCMV or saline. Five days later, each mouse underwent drilling, microdebrider, coblation, and electrocautery procedures. Particle size distribution and PM2.5 (particulate matter <2.5 µm) concentration were determined with a scanning mobility particle sizer and an aerosol particle sizer in the range of 15 nm to 32 µm. Aerosolized samples from these procedures were collected with an Aerosol Devices BioSpot sampler for viral titer based on polymerase chain reaction and for viable virus through viral culture. Results: As compared with the background aerosol concentrations, coblation and electrocautery showed statistically significant increases in airborne aerosols (Tukey‐adjusted P value <.040), while microdebrider and drilling at 30, 000 rpm did not (.870 < Tukey‐adjusted P value <. 930). We identified viral DNA in samples from coblation and drilling procedures, although we did not identify viable viruses in aerosol samples from any of the 4 procedures. Conclusion: Coblation and electrocautery procedures generate >100‐fold increases in aerosol concentrations over background; only coblation and drilling produce aerosolized viral DNA. The high concentration of aerosols from coblation and electrocautery suggests the need for appropriate safeguards against particle exposure to health care workers. The presence of viral DNA from drilling and coblation procedures warrants the need for appropriate protection against droplet and aerosol exposure.